Power Trading and Congestion Management Through Real Power Rescheduling Using Unified Power Flow Controller - S.K. Gupta; R. Bansal; Partibha Sharma; Mukesh Saini (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2014)
Congestion is termed as the operating condition in which there is not enough transmission capacity to implement all the desired transactions. This paper deals with the power trading in electricity market to ensure regular supply at competitive rates. Bidding process of 75 Indian bus systems is analyzed. It is shown that how can congestion cost can be addressed through active power rescheduling with transmission line constraints using Unified power flow controller.